Effects of different frequency of electromagnetic field on cell proliferation, differentiation and mineralization - Koh, Boon Sheng (2018)
Over the decades, there is a rise of using Electromagnetic fields (EMFs) to treat fractures and other bone diseases. One of them would be the non-unions fracture, which requires an extended amount of time for the fractured bone to heal. This would normally be seen in elderly whom suffered from broken bones as the percentage of non-union can increase up to 30%. The conventional methods for treating bone defects are usually through surgery such as bone grafting and plate fixation. Although in the past it had been successful in treating the fractured bones, it has also been proved as ineffective for several patients and various complications occurred. Thus, an alternative minimally invasive method has been studied to help in treating bone-related illness such as using EMFs treatment to enhance the maturation of osteoblastic cells. Hence, this project aims to investigate the effects of the varying frequency of EMFs on proliferation, maturation and mineralization potentials of MC3T3 cells, an osteoprogenitor cell derived from the mice. Cells were exposed to with EMFs with frequencies of 5Hz, 50Hz and 100Hz for 30 minutes per day for 28days at the electromagnetic field intensity of 0.6 mT in the absence or presence of an osteogenic medium. The assays conducted over the experimental duration shows greater cell density and higher DNA content measurement in cells that were exposed to EMF and reached 80%-100% confluency by day 7. The results give a better understanding of the effects of Pulsed Electromagnetic Field (PEMF) on bone tissues where it requires both the presence of osteoinductive medium and an optimal PEMF induction for improved bone regeneration. The results from this study also show that the optimal PEMF frequency for a higher rate of cell differentiation and mineralization is 50Hz. The cells that are exposed to 50Hz of electromagnetic field shows higher cell differentiation compare to 100Hz, 5Hz, and control (not exposed to PEMF).